2014
DOI: 10.1016/j.jelechem.2014.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of effective surface area for electrochemical reaction derived from mass transport property

Abstract: The effective surface area, eff S , for electrochemical reaction at a Pt electrode was analyzed using mass transport property as a probe. This parameter is different to the socalled electrochemical surface area (ECA), which is usually obtained from the amount of protons which are underpotentially deposited, UPD H , or by CO stripping. The analysis was done using both experimental and numerical methods. In experiments, a rotating disk electrode (RDE) was used under the conditions where the Pt surface can be par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Similar results of particle size reduction in titanium and antimony had been reported by our group in previous studies [11,12]. Moreover, in nickelcadmium batteries, cadmium is used as negative electrode plate, which oxidised and release electrons during discharging, thus reduction in particle size of cadmium powder after biofield treatment may increases the specific energy of batteries [32,33] Furthermore, Iden et al reported that increase in surface area improves the kinetics of electrochemical reactions in batteries [34]. Thus, it is assumed that biofield treated cadmium could be more useful in electrochemical application as compared to control.…”
Section: Particle Size and Surface Area Analysissupporting
confidence: 82%
“…Similar results of particle size reduction in titanium and antimony had been reported by our group in previous studies [11,12]. Moreover, in nickelcadmium batteries, cadmium is used as negative electrode plate, which oxidised and release electrons during discharging, thus reduction in particle size of cadmium powder after biofield treatment may increases the specific energy of batteries [32,33] Furthermore, Iden et al reported that increase in surface area improves the kinetics of electrochemical reactions in batteries [34]. Thus, it is assumed that biofield treated cadmium could be more useful in electrochemical application as compared to control.…”
Section: Particle Size and Surface Area Analysissupporting
confidence: 82%
“…Although there is much work in the literature assessing the performance of platinum toward the hor/her it is now well recognized that mass transport masks the true activity of platinum for this reaction, and the measured “exchange current densities” are too low in many papers. , This effect is illustrated in Figure in which the her/hor polarization plots are presented for a range of different electrochemical techniques transformed into specific activity (current density per real surface area). These techniques cover a wide range of mass transport regimes, in increasing order from microelectrodes with high surface area platinum catalyst ( R f = 30) in contact with Nafion or acid, a 50 μm platinum microelectrode ( R f ≈1) in contact with aqueous acid, to a Pt rotating disk electrode ( R f ≈ 1, 7200 rpm) in contact with 0.1 mol dm –3 HClO 4 , to a single platinum particle (450 nm in diameter) in acid to results obtained utilizing our floating electrode technique , ( R f ≈ 1) for an electrode in 1 mol dm –3 HClO 4 . It is clear that there is a significant spread of results, but what is also clear is that mass transport effects occur even when the electrode is polarized at potentials at which the current is a small fraction of the mass transport limited current.…”
Section: Resultsmentioning
confidence: 99%
“…This alteration in the diffusion field and detection volume affects the mass transport of ions to the electrode surface. 32…”
Section: Resultsmentioning
confidence: 99%
“…This alteration in the diffusion field and detection volume affects the mass transport of ions to the electrode surface. 32 Evaluating these fluorescence emissions 30 s after the voltage was applied and using the calibration curve to convert the fluorescence ratio to pH, yields the result shown in Fig. 4B.…”
Section: Electrochemical Induction Of An Expansive Ph Rangementioning
confidence: 99%